Relationship between placental autophagy and inflammasome activities with morbidity of extremely preterm infants - Deliloğlu, Burak; Tüzün, Funda; Aysal, Anıl; Duman, Nuray; Özkan, Hasan; Özer, Erdener (The Turkish Journal of Pediatrics, 2022)
Background. The placenta is the major regulatory element of the in-utero environment, and alterations in placental cellular functions in infection, inflammation, and hypoxemia lead to adverse preterm birth outcomes. The importance of regulation of autophagy and inflammasome activities has been shown in the pathogenesis of morbidities in immature animal models. This study aimed to determine the relationship between placental autophagy and inflammasome activities with morbidity in extremely preterm infants. Methods. Premature infants born between 24th to 29th gestational weeks were evaluated prospectively. Placental LC3B and NLRP3 immunostainings were performed to assess autophagy and inflammasome activities. Preterm morbidities including respiratory distress syndrome (RDS), patent ductus ateriosus: (PDA), intraventricular hemorrhage (IVH), necrotizing enterocolitis (NEC), periventricular leukomalacia (PVL), sepsis, bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP) and mortality were evaluated. Results. Fifty-nine infants with a mean gestational age of 26.9 ± 1.5 weeks were included. Anti-LC3B staining scores were moderate or intense positive in 75% of the placentas. Anti-LC3B activity was not associated with the existance of evaluated neonatal morbidities or mortality. Autophagy and inflammasome coexistence were demonstrated in 35 placentas (59.3%). Anti-NLRP3 staining score was moderate or intensely positive in 75% of the placentas. Infants with BPD had a lower rate of positive anti -NLRP3 staining than infants without BPD (42.9 vs 57.1%, p=0.048). Infants who had hemodynamic significant patent ductus arteriosus (hsPDA) and surgical- NEC showed significantly intense anti-NLRP3 staining compared to infants who did not (18.8% vs 0%, p= 0.027 and 33% vs 7.5%, p=0.048 respectively). Conclusions. The results showed that autophagy and inflammatory activities were present in varying amounts in the placenta of preterm infants. Association of decreased or increased rates of inflammasome activities with certain diseases such as BPD, hsPDA and surgical-NEC indicates the role of the intrauterin inflammatory process and the importance of critical balance in inflammation. Because of the complex pathophysiology of preterm morbidities, placental autophagy and inflammasome activities seem worthy of further investigation.